Resampling methods a practical guide to data analysis - Good, Phillip I. 1937- (Birkhäuser, 2005)
"...the author has packaged an excellent and modern set of topics around the development and use of quantitative models.... If you need to learn about resampling, this book would be a good place to start." - Technometrics (Review of Second Edition) This thoroughly revised and expanded third edition is a practical guide to data analysis using the bootstrap, cross-validation, and permutation tests. Only requiring minimal mathematics beyond algebra, it provides a table-free introduction to data analysis utilizing numerous exercises, practical data sets, and freely available statistical shareware
Auch als Internetausgabe
Keywords: Resampling; Einführung